2013
DOI: 10.1007/s00244-013-9967-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atrazine, Glyphosate and Quinclorac on Biochemical Parameters, Lipid Peroxidation and Survival in Bullfrog Tadpoles (Lithobates catesbeianus)

Abstract: Increased use of pesticides worldwide has led to damage not only to natural ecosystems but also to nontarget species. This study assessed the effects of different concentrations of the herbicides atrazine, glyphosate, and quinclorac on biochemical parameters, lipid peroxidation, and survival in tadpoles of Lithobates catesbeianus (bullfrog). Two hundred eighty-eight tadpoles were acquired from a frog farm in the south of Brazil. All animals were kept in aquariums under controlled laboratory conditions for 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 39 publications
2
36
1
Order By: Relevance
“…However, studies on nutritional requirements of the species are still in infancy. Several studies have been conducted for determination of the optimum dietary protein and lipid levels, protein/lipid ratio, carbohydrate/lipid ratio and dietary methionine requirement of the species (Carmona‐Osalde, Olvera‐Novoa, Rodríguez‐Serna & Flores‐Nava, ; Dornelles & Oliveira, ; Huang, Zhang, Wang, Song & Huang, ; Olvera‐Novoa, Ontiveros‐Escutia & Flores‐Nava, ; Zhang, Huang et al., ; Zhang, Feng et al., ). There are several reports indicating the essentiality of GAA supplementation in plant protein‐based diets for broilers (Heger et al., ; Metwally, Ibrahim & Khater, ; Michiels et al., ; Mousavi, Afsar & Lotfollahian, ; Ringel et al., ; Wang, Shi, Shan & Zhang, ); however, to the best of our knowledge, there is no available research on surveying the effects of GAA inclusion in plant‐based diets for aquatic animals.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on nutritional requirements of the species are still in infancy. Several studies have been conducted for determination of the optimum dietary protein and lipid levels, protein/lipid ratio, carbohydrate/lipid ratio and dietary methionine requirement of the species (Carmona‐Osalde, Olvera‐Novoa, Rodríguez‐Serna & Flores‐Nava, ; Dornelles & Oliveira, ; Huang, Zhang, Wang, Song & Huang, ; Olvera‐Novoa, Ontiveros‐Escutia & Flores‐Nava, ; Zhang, Huang et al., ; Zhang, Feng et al., ). There are several reports indicating the essentiality of GAA supplementation in plant protein‐based diets for broilers (Heger et al., ; Metwally, Ibrahim & Khater, ; Michiels et al., ; Mousavi, Afsar & Lotfollahian, ; Ringel et al., ; Wang, Shi, Shan & Zhang, ); however, to the best of our knowledge, there is no available research on surveying the effects of GAA inclusion in plant‐based diets for aquatic animals.…”
Section: Introductionmentioning
confidence: 99%
“…As a general consideration, the absence of mortality rate in the different groups tested (both control and exposed) indicates a good quality of the experimental conditions and confirms the sub-lethal concentrations of GBHs. Similarly, no mortality has been observed in experiments using tadpoles exposed to ecologically relevant concentrations of several herbicides (Dornelles and Oliveira, 2014; Wilkens et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The differences between ponds were largely in areas associated with glycogen/carbohydrates and symmetric phosphate stretching, with some protein contribution. Glycogen, and to a lesser extent, protein, is utilised as an energy source in amphibians and may be depleted in response to stressful situations, such as exposure to environmental contaminants, as the organism attempts to maintain homeostasis by compensatory metabolic mechanisms, thus utilising energy reserves4445. Regions of the IR spectrum associated with carbohydrates, particularly glycogen showed marked decreases in the peak heights in spectra of tadpoles from PF and WH (both sites with relatively lower water quality) in comparison to those from CT (higher water quality status).…”
Section: Discussionmentioning
confidence: 99%
“…Regions of the IR spectrum associated with carbohydrates, particularly glycogen showed marked decreases in the peak heights in spectra of tadpoles from PF and WH (both sites with relatively lower water quality) in comparison to those from CT (higher water quality status). Several studies have measured glycogen levels in tissues of both larval and adult amphibians following exposure to various environmental contaminants, including pesticides such as atrazine444647, glyphosate44, quinclorac44, basudin48, naphthenic acids45 and PAHs49. In general, these studies found depleted levels of glycogen in response to pesticide exposure, although not in all cases46.…”
Section: Discussionmentioning
confidence: 99%